OTHER and ELSE : Same difference ? Deux expressions de l’altérité en anglais - Martine Schuwer; Blandine Pennec (Anglophonia)
In terms of qualifiers, other and else may both express the notion of otherness in English. At the semantic level, they seem to be very similar in the sense that they share the same notional feature of “presupposition”. It is indeed bv reference to a first element that a second one may be qualified with other or else. However, other and else differ in terms ofsyntactic behaviour, thus denoting distinct underlying operations, and probably accountingfor their differing values in context. According to their linguistic environment, other and else may in fact either bring a qualitative or a quantitative determination. Carried out within the framework of the Theory ofEnunciative Operations, this study proposes a model of the various values corresponding to either determining operation.